2005
DOI: 10.2337/diacare.28.2.385
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome and 11-Year Risk of Incident Cardiovascular Disease in the Atherosclerosis Risk in Communities Study

Abstract: OBJECTIVE -To assess the magnitude of the association between the National Cholesterol Education Program's Third Adult Treatment Panel Report (ATP III) definition of the metabolic syndrome and cardiovascular disease (CVD).RESEARCH DESIGN AND METHODS -Cox regression was used to estimate the relative risk of incident coronary heart disease (CHD) and stroke among 12,089 black and white middle-aged individuals in the Atherosclerosis Risk in Communities (ARIC) study.RESULTS -The metabolic syndrome was present in ϳ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
547
5
30

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 872 publications
(626 citation statements)
references
References 35 publications
44
547
5
30
Order By: Relevance
“…Initial studies adjusting for traditional cardiovascular risk factors suggested that the metabolic syndrome construct carries prognostic weight 7, 25, 26. More recent studies accounting for the actual components of the metabolic syndrome imply that the metabolic syndrome construct does not add explanatory power beyond that afforded by its components 27. The current analysis supports the latter notion with regard to sudden cardiac death.…”
Section: Discussionsupporting
confidence: 57%
“…Initial studies adjusting for traditional cardiovascular risk factors suggested that the metabolic syndrome construct carries prognostic weight 7, 25, 26. More recent studies accounting for the actual components of the metabolic syndrome imply that the metabolic syndrome construct does not add explanatory power beyond that afforded by its components 27. The current analysis supports the latter notion with regard to sudden cardiac death.…”
Section: Discussionsupporting
confidence: 57%
“…Although justification by the same cutoff point during fasting is still under debate, the data of non-fasting triglycerides can be used because it is a significant predictor for ischemic heart disease. 33 Therefore, we assessed HbA 1c instead of fasting glucose, non-fasting triglycerides and HDL cholesterol and used a 'modified' MS definition rather than the standard definition. Third, we could not compare the adiponectin levels before and after medication in the present cross-sectional, observational study of chronic hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐density lipoprotein was calculated using the Friedewald equation. Serum glucose was measured by the hexokinase‐6‐phosphate dehydrogenase method 26. Trained clinical staff measured waist circumference at the umbilical level to the nearest cm.…”
Section: Methodsmentioning
confidence: 99%